Diagnostic Accuracy of CT Angiography in Stable Patients Suspected of Obstructive Coronary Artery Disease - Yaqoob, Rizwan Ahmed; Arshad, Muhammad; Hameed, Ali (Biological and Clinical Sciences Research Journal, 2025)
Coronary artery disease (CAD) remains a leading cause of morbidity and mortality worldwide. Accurate diagnosis in stable patients at high risk of obstructive CAD is critical for timely intervention. While invasive coronary angiography (ICA) is the gold standard, coronary computed tomography angiography (CCTA) is increasingly being used as a non-invasive alternative with promising diagnostic value and fewer procedural risks. Objective: To analyze and compare the diagnostic accuracy and safety of CCTA and ICA in stable patients at high risk of obstructive CAD. Methods: A prospective study was conducted in the Department of Cardiology, Punjab Institute of Cardiology, Lahore, between May 2023 to May 2025. Eligible patients included those with left ventricular ejection fraction (LVEF) <50% and typical angina symptoms, with pre-test probability of obstructive CAD between 50–85% along with a positive functional test, or >85% regardless of functional testing. A total of 100 patients were consecutively enrolled and divided equally: Group A (n=50) underwent CCTA, and Group B (n=50) underwent ICA. Outcomes were evaluated for diagnostic utility, frequency of non-actionable procedures, and safety endpoints. Statistical analysis included chi-square testing and comparison of proportions, with p<0.05 considered significant. Results: Use of CCTA significantly reduced the rate of invasive procedures by 65% (p<0.0001) and decreased non-actionable ICAs by 90% (p<0.0001). At one-year follow-up, major adverse cardiac outcomes—including mortality, acute coronary syndrome, urgent revascularization, stroke, and cardiac-related hospital admission—were observed in 20 (40%) patients in Group A and 21 (42%) in Group B (p=0.91). Conclusion: CCTA provides a safe and effective alternative to ICA for diagnosing obstructive CAD in stable high-risk patients, reducing unnecessary invasive procedures without compromising clinical outcomes.